2013
DOI: 10.1111/bjop.12054
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory assessment of theory of mind and psychological impairment in patients with bulimia nervosa

Abstract: This study aimed to investigate psychosocial functioning and different dimensions of theory of mind (ToM) in people with bulimia nervosa (BN) and Eating Disorder Not Otherwise Specified-BN type (EDNOS-BN). Psychosocial functioning and ToM were assessed in a sample of young adult females, 16 BN and 16 EDNOS-BN outpatients and 16 healthy controls (HCs). They were assessed using the Eating Disorder Inventory-Symptom Checklist-2 (EDI-2 SC) for evaluating psychological traits associated with eating disorders; the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 67 publications
4
17
0
Order By: Relevance
“…Moreover, females participants were resulted significantly more prone to eat to cope with negative affective states than males. This result was supported by other studies that showed that females with binge eating behavior were more likely to have higher levels of emotional eating (Laghi et al, 2013, 2014, Waller & Osman, 1998Waters et al, 2001).…”
Section: Introductionsupporting
confidence: 81%
“…Moreover, females participants were resulted significantly more prone to eat to cope with negative affective states than males. This result was supported by other studies that showed that females with binge eating behavior were more likely to have higher levels of emotional eating (Laghi et al, 2013, 2014, Waller & Osman, 1998Waters et al, 2001).…”
Section: Introductionsupporting
confidence: 81%
“…Here too, even if some studies suggest impairment in this process (Smeets et al, 1999; Cooper and Mohr, 2012; Laghi et al, 2013), future studies should identify the extent of the impairment and its relation with both memory processes and the manipulation of bodily representations.…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, recent studies underline a moderate role of the gender in adolescents with AN, as well as negative perceptions of their family functioning and good performances in mindreading tasks, while bulimic patients revealed an impairment in their theory of mind (Laghi et al, 2014b(Laghi et al, , 2015a(Laghi et al, , 2015b.…”
Section: Anorexia Nervosa and Bulimia Nervosamentioning
confidence: 99%